2010
DOI: 10.1515/bc.2010.042
|View full text |Cite
|
Sign up to set email alerts
|

Tissue kallikrein in cardiovascular, cerebrovascular and renal diseases and skin wound healing

Abstract: Tissue kallikrein (KLK1) processes low-molecular weight kininogen to produce vasoactive kinins, which exert biological functions via kinin receptor signaling. Using various delivery approaches, we have demonstrated that tissue kallikrein through kinin B2 receptor signaling exhibits a wide spectrum of beneficial effects by reducing cardiac and renal injuries, restenosis and ischemic stroke, and by promoting angiogenesis and skin wound healing, independent of blood pressure reduction. Protection by tissue kallik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 123 publications
6
81
1
Order By: Relevance
“…However, numerous other studies support the results of the present study, indicating that TK exerts a neuroprotective effect in ischemic injury (24,25,46,47). This type of protective effect may be associated with the following factors: i) The actions of TK can be mediated by kinin B 2 receptor activation without kinin formation (48); ii) kallikrein-induced anti-inflammation is dependent on kinin B 2 receptor activation and nitric oxide formation (24); iii) upregulation of endothelial nitric oxides resulted in dilation of cerebral arterial vessels, which is critical in maintaining the cerebral blood flow and conducive to the removal of inflammatory mediators (25); and iv) in the early period following cerebral I/R, kallikrein induced angiogenesis and improved the regional cerebral blood flow in the peri-infarction region, and further reduced the infarction volume and improved the neurological deficits (46).…”
Section: Discussionsupporting
confidence: 82%
“…However, numerous other studies support the results of the present study, indicating that TK exerts a neuroprotective effect in ischemic injury (24,25,46,47). This type of protective effect may be associated with the following factors: i) The actions of TK can be mediated by kinin B 2 receptor activation without kinin formation (48); ii) kallikrein-induced anti-inflammation is dependent on kinin B 2 receptor activation and nitric oxide formation (24); iii) upregulation of endothelial nitric oxides resulted in dilation of cerebral arterial vessels, which is critical in maintaining the cerebral blood flow and conducive to the removal of inflammatory mediators (25); and iv) in the early period following cerebral I/R, kallikrein induced angiogenesis and improved the regional cerebral blood flow in the peri-infarction region, and further reduced the infarction volume and improved the neurological deficits (46).…”
Section: Discussionsupporting
confidence: 82%
“…The KKS exerts physiological effects through binding of kinin peptides to the bradykinin 1 and bradykinin 2 receptors [7], [8]. In addition to the blood pressure lowering effects to balance the renin-angiotensin system [9], the KKS is proposed to improve insulin sensitivity [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…these could lead to variability in phenotypes and disease susceptibility. Various studies have reported involvement of keratinization, cadherins and serine proteases (Chao et al 2010) in skin physiology. It is possible that CNVRs in these enriched processes might explain the observable wide spectrum of skin pigmentation across Indian populations.…”
Section: Discussionmentioning
confidence: 99%